Bouveret Syndrome: A Systematic Review of Endoscopic Therapy and a Novel Predictive Tool to Aid in Management. Issue 9 (October 2020) - Ong, John; Swift, Carla; Stokell, Benjamin G.; Ong, Sharon; Lucarelli, Pierino; Shankar, Arun; Rouhani, Foad J.; Al-Naeeb, Yasseen
Abstract : Background and Goals: Bouveret syndrome is characterized by gastroduodenal obstruction caused by an impacted gallstone. Current literature recommends endoscopic therapy as the first line of intervention despite significantly lower success rates compared with surgery. The lack of treatment efficacy studies and the paucity of clinical guidelines contribute to current practices being arbitrary. The aim of this systematic review was to identify factors that predict outcomes of endoscopic therapy. Subsequently, a predictive tool was devised to predict the success of endoscopic therapy and recommendations were proposed to improve current management strategies of impacted gallstones in the upper gastrointestinal tract. Methods: A systematic search of PubMed, Medline, Cochrane, and Scopus was performed for articles that contained the terms "Bouveret syndrome, " "Bouveret's syndrome, " "gallstone" AND "gastric obstruction" and "gallstone" AND "duodenal obstruction" that were published between January 1, 1950 to April 15, 2018. Articles were reviewed by 3 reviewers and raw data collated. χ 2 and Kolmogorov-Smirnov tests were used to test associations between predictors and endoscopic outcomes. A logistic regression model was then used to create a predictive tool which was cross validated. Results: Failure of endoscopic therapy is associated with increasing gallstone length ( P <0.0001) and impaction in the distal duodenum ( P <0.05). Using multiple endoscopic modalities is associated with better success rates ( P <0.05). The novel predictive tool predicted success of endoscopic therapy with an area under the receiver operating characteristic score of 0.86 (95% confidence interval: 0.79-0.94). Conclusion: In Bouveret syndrome, a selective approach to endoscopic therapy can expedite definitive treatment and improve current management strategies. Abstract : Supplemental Digital Content is available in the text.